Dynamic planning method of economic operation optimization model. (22nd November 2020) - Jing, Jing
Abstract: Enterprise dynamic planning is a branch of operations research and multi‐stage decision‐making processes. This method can be used to solve multi‐objective decision‐making problems, thereby optimizing the overall effect of the system. Aiming at the dynamic programming method of economic operation optimization model, this article studies a multi‐objective dynamic programming algorithm and improves the algorithm. Taking the optimization arrangement of enterprise production plan as an example, according to the production capacity, production cost and inventory cost of the enterprise, a dynamic planning method is adopted to establish a production plan arrangement model. The experimental results show that using the method proposed in this article to dynamically plan the economic operation optimization model can not only improve the convergence of the results but also improve its accuracy. This result solves the optimization problem of the enterprise's product production plan.